The simulation analysis of torque ripple reduction by using optimal voltage vector in DTC fed by five-level CHB inverter - Siti Azura Binti Ahmad Tarusan; Auzani Jidin; Mohd Luqman M. Jamil (Institute of Advanced Engineering and Science, 2020)
In this paper, the improvement of torque ripple reduction will be focused based on the optimal voltage vector. This is attained by using five-level CHB inverter that applies in DTC drive control as a proposed method. The analysis is performed and simulated by using MATLAB/Simulink. In order to support the analysis, the comparison is realized between proposed method and conventional method which it applies two-level inverter. It will be analysed at constant torque region or steady-state operation on different range of operating speed which the speed is controlled by adjusting the motor load. Meaning that, the speed controller is neglected during analysis. Nevertheless, the adjustment of motor load must be applicable to the optimal voltage vector. The look-up table of five-level CHB inverter will become a guideline to select the optimal voltage vector. Therefore, it can maintain the simple structure of DTC hysteresis-based that fed by using five-level CHB inverter. As a result, the torque ripple can be minimized and torque capability can be retained even at low operating speed compared to the conventional DTC.